Description of a New Genus and Species of Semi-Aquatic Rodent (Cricetidae, Sigmodontinae, Ichthyomyini) from the Southern Peruvian Andes - Horacio Zeballos; Alexander Pari; César E. Medina; Kateryn Pino; Sandra Arias; Alayda L. Arce; Fiorella N. Gonzales (Diversity, 2025)
We describe a new genus and species of the tribe Ichthyomyini (Rodentia: Sigmodontinae) based on three specimens collected in Machupicchu, Cusco, in the southern Peruvian Andes. Our study includes a comprehensive morphological analysis of 201 specimens representing all recognized species, employing multivariate statistics (principal component analysis) of external and cranial measurements, as well as phylogenetic methods. We used maximum parsimony for morphological data and concatenated molecular datasets (Cytochrome b [17 species], IRBP [15 species], and RAG1 [11 species]) analyzed via maximum likelihood and Bayesian inference. The new genus and species exhibit an allopatric distribution relative to other Ichthyomyini and are distinguished by the following combination of traits: dull slate-gray dorsal fur, lighter ventrally without contrast to the dorsum; incomplete philtrum; vestigial pinna concealed within head fur; long, broad hindfeet with a well-developed fringe of stiff hairs and brown soles; laterally compressed tail exceeding head-body length; type 1 carotid circulation pattern; absence of the orbicular apophysis of the malleus; presence of posteroloph and posterolophid in M1, M2, m1, and m2; unilocular hemiglandular stomach (non-reduced).